Telomere tracking from birth to adulthood and residential traffic exposure - Esmée M. Bijnens; Maurice P. Zeegers; Catherine Derom; Dries S. Martens; Marij Gielen; Geja J. Hageman; Michelle Plusquin; Evert Thiery; Robert Vlietinck; Tim S. Nawrot (BMC Medicine, 2017)
Abstract Background Telomere attrition is extremely rapid during the first years of life, while lifestyle during adulthood exerts a minor impact. This suggests that early life is an important period in the determination of telomere length. We investigated the importance of the early-life environment on both telomere tracking and adult telomere length. Methods Among 184 twins of the East Flanders Prospective Twin Survey, telomere length in placental tissue and in buccal cells in young adulthood was measured. Residential addresses at birth and in young adulthood were geocoded and residential traffic and greenness exposure was determined. Results We investigated individual telomere tracking from birth over a 20 year period (mean age (SD), 22.6 (3.1) years) in association with residential exposure to traffic and greenness. Telomere length in placental tissue and in buccal cells in young adulthood correlated positively (r = 0.31, P < 0.0001). Persons with higher placental telomere length at birth were more likely to have a stronger downward shift in telomere ranking over life (P < 0.0001). Maternal residential traffic exposure correlated inversely with telomere length at birth. Independent of birth placental telomere length, telomere ranking between birth and young adulthood was negatively and significantly associated with residential traffic exposure at the birth address, while traffic exposure at the residential address at adult age was not associated with telomere length. Conclusions Longitudinal evidence of telomere length tracking from birth to adulthood shows inverse associations of residential traffic exposure in association with telomere length at birth as well as accelerated telomere shortening in the first two decades of life.